Energy, knowledge and economic growth - John Foster (Max Planck Institute of Economics, 2013)
It is argued that the explosive growth experienced in much of the World since the middle of the 19th Century is due to the exploitation and use of fossil fuels which, in turn, was made possible by capital good innovations that enabled this source of energy to be used effectively. Economic growth, it is argued, has been due to an autocatalytic co-evolution of energy use and the application of new knowledge relating to energy use. A simple evolutionary macroeconomic model of economic growth is developed and tested using almost two centuries of British data. The empirical findings strongly support the hypothesis that growth has been due to the presence of a 'super-radical innovation diffusion process.' Also, the evidence suggests that large and sustained movements in energy prices have had a very significant long term role to play. The paper concludes with an assessment of the implications of the findings for the future prospects of economic growth in Britain and the possible lessons that can be learned about the future of the global economy.
Keywords: 330; Wirtschaftswachstum; Evolutionsökonomik; Investitionsgüter; Innovationsdiffusion; Energiepreis; Großbritannien